A phantom menace: Is Russian LNG a threat to Russia's pipeline gas in Europe? - Vitaly Yermakov; Jack Sharples (The Oxford Institute for Energy Studies, 2021)
Russian gas exports to Europe have traditionally meant one thing: pipeline supplies from Gazprom. But since December 2017, Russian LNG cargoes from the Yamal LNG project led by the private Russian company, Novatek, have increasingly made their mark, especially in North-Western Europe. Despite the original intention that Yamal LNG cargoes would be predominantly shipped to Asia - via the Northern Sea Route in the summer and via transshipment in Europe in the winter - Yamal LNG cargoes have increasingly remained in Europe, prompting debates over possible competition between the two sources of Russian gas. In our analysis, we find although Yamal LNG cargoes may indeed compete with Gazprom's pipeline supplies in Europe, once the cargoes have left Yamal not only does the Russian government not have the ability to 'manage' competition between Gazprom and Yamal LNG, but those Yamal LNG cargoes become (to all intents and purposes) no different to any other LNG cargoes with which Gazprom's pipeline supplies compete. We conclude that the Russian government has implicitly recognised this, and has chosen to support the expansion of Russia's LNG export capacity even at the potential expense of competition with Gazprom's pipeline supplies, as this is preferable to simply ceding market share to other non-Russian LNG suppliers.
Keywords: 330; Gazprom; LNG; Novatek; Pipeline; Russia